Topological doping effects in 2D chalcogenide thermoelectrics. (16th July 2018) - Dun, Chaochao; Liu, Yu; Al-Qawasmeh, Ahmad; Hewitt, Corey A; Guo, Yang; Xu, Junwei; Jiang, Qike; Wang, Jian; Marcus, Gabriel; Cadavid, Doris; Montgomery, David; Wang, Hongzhi; et al.
Abstract: The topological nature of two-dimensional (2D) chalcogenide platelets, can present novel opportunities in thin, flexible thermoelectrics. In this work, metal dopants are added to the reactive edges of 2D Bi2 Te3 platelets. We show that along this active edge, an atomically well-ordered heterojunction is formed and facile charge exchange is created, onto the platelet and proximal to its known topological states. Temperature dependent conductivity suggests that local band bending across the interface may act as an injection energy filter for dopant-originated carriers. Moreover, as carrier density increases with increasing edge-dopant, carrier scattering does not appear to increase dramatically. As a result, an apparent decoupling between electrical conductivity and Seebeck coefficient occurs, leading to a surprisingly high power factors (PF): For example, the PF increases in Bi2 Te3 platelets by eight times when doped with Cu. First principles calculations show that the electronics of the semiconductor-metal interfaces are quite different for edge and facial configurations, thus the site of metal dopant is believed to play an important role in the expected thermoelectric performance. Finally, this work suggests that the topological sensitivity of dopant placement should be considered in the rational design of high performance thermoelectric composites.